The ecological nature of whole river macrosystems: new perspectives from the riverine ecosystem synthesis - Thorp, James H.; Thoms, Martin C.; Delong, Michael D.; Maasri, Alain (Frontiers in Ecology and Evolution, 2023)
Opportunities to understand and protect natural aquatic diversity in both relatively pristine and managed rivers can be enhanced with a comprehensive, system-wide understanding of a river’s hydrogeomorpholgy and its effects on ecological structure and functioning from the river's headwaters to its terminus in an ocean, lake, or natural endorheic basin. While a moderate number of macrosystem ecology studies have been undertaken recently in headwaters, comparable ecological approaches to studying whole rivers or at least their larger components from upstream to downstream are relatively rare. This is partially correlated with the paucity of applicable river ecosystem models developed over the last half century which could otherwise provide diverse, testable hypotheses. This manuscript focuses on a 15+ year analysis and expansion of the hypotheses and system-wide applicability of one lotic model, the Riverine Ecosystem Synthesis, or RES (Thorp et al. 2006, 2008). Where appropriate, we also analyze aspects of several other models pertaining to river ecology and propose four additional whole river tenets to the RES, thereby increasing the number in the revised RES to 21.